Selective purification of the thiol peptides of myosin - Weeds, A. G. (1968)
1. A method for selective purification of thiol peptides is described. Thiol groups in a protein are treated with radioactive cystine by disulphide–thiol interchange. The labelled cystine peptides in a digest can then be fractionated for peptide `maps'. Performic acid oxidation of paper strips containing the radioactive peptides followed by further ionophoresis yields the purified cysteic acid peptides. 2. The thiol peptides in a peptic digest of cystine-exchanged myosin were purified in this way, and their amino acid sequences were determined. 3. The conclusion that myosin contains at least 16, and probably between 20 and 22, unique thiol sequences indicates that the molecule consists of two chemically equivalent components.